Student Perceptions on the Effectiveness of Using Tell Me More for Pronunciation Learning - Arulselvi, Uthayakumaran; Hafizoah, Kassim (Universiti Malaysia Pahang, 2018)
This paper reports students’ perceptions of the effectiveness of using Tell Me More (TMM) as a pronunciation learning software. A mixed method design was employed to find out how the students perceived TMM, a language learning software that was developed to enhance language skills that are needed to communicate. In this study, the emphasis is given on the oral exercises in TMM specifically word, sentence, and phonetics pronunciations. The participants were 28 students of a technical university in Malaysia, and the study was conducted to explore the pronunciation issues surrounding the utilization of TMM. The data from TMM was collected using stimulated recall, and all 28 students were interviewed, to pursue in-depth information on student perceptions. The findings indicated that most of the students had mixed perceptions of the effectiveness of using TMM as a pronunciation learning software.